Neural Networks for Cooperative Control of Multiple Robot Arms - Li, Shuai (SpringerBriefs in Computational Intelligence,, 2018)
This is the first book to focus on solving cooperative control problems of multiple robot arms using different centralized or distributed neural network models, presenting methods and algorithms together with the corresponding theoretical analysis and simulated examples. It is intended for graduate students and academic and industrial researchers in the field of control, robotics, neural networks, simulation and modelling.